The Effect of the Solvents on Electrical Properties of POT Conducting Polymer - Manal Rajab; K. M. Ziadan (Mechanics of Advanced Composite Structures)
In this research, the preparation conducting polymer poly(O-Toluidine) emeraldine salt (ES) doped with HCL (POT/HCL) by oxidizing polymerization external doping by DBSA the effect of the solvent on the electrical characterization of Poly (O-toluidine) was studied.POT (EB) powder was completely dissolving in all solvents such as chloroform, formic acid, Toluene, and meta-cresol. The morphology and composition of POT were measured by SEM and EDX. Two-probe techniques were used to calculate electrical conductivity; an interdigitated finger electrode was used to measure electrical conductivity.  The effect of temperatures on electrical conductivity was also studied to provide heating in the range of (303-373 K) and used to the found activation energy of (POT) in a different solvent.